STUDYING THE EFFECT OF CUTOUTS ON THE COMPOSITE LAMINATE PLATES - Y. R, Arz; nan, nan (Anbar Journal of Engineering Sciences, 2008)
The aim of current work is to investigate the tensioned composite plates with two types of cutouts. Many industrial applications use composite matrix with reinforcement fiber to obtain better properties. The objective of this work is divided into two parts, first the experimental work covers the measuring of the normal strain (εx) at the edges of (circular & square) holes that are perpendicular to the direction of the applied loads with different number of layers and types of cutouts of composite materials by using strain gages technique under constant tensile loads to compare with the numerical results. The second part is numerical work, which involves studying the static analysis of symmetric square plates with different types of cutout (circular – square). In static analysis, the effect of the following design parameters on the maximum stress (σx), strain (εx) and deflection (Ux) is studied. This part of investigation was achieved by using the software finite element package (ANSYS 5.4).